Pengaruh Kegiatan Outbound ke Museum terhadap Peningkatan Hasil Belajar Mata Pelajaran IPS Siswa Kelas IV B SD Islam Darul Mustafa - Sholeh, Asmar; Indra, Cahaya; Shakila, Farrah Adli; Lubis, Muthia Fadilaturrizqi; Siregar, Putri Novia Ramayani; Yusnaldi, Eka (Pusdikra-Publishing.com, 2025)
Outbound activities to museums as an innovative learning approach offer interactive and fun learning experiences. In social studies learning, this method plays an important role in changing abstract material into more concrete and meaningful ones. This research aims to determine the effect of outbound activities to the museum on the learning outcomes of class IV B students at SD Islam Darul Mustafa. The issues raised include the effectiveness of outbound activities in improving student learning outcomes, differences in motivation before and after the activity, as well as identifying the aspects of the activity that contribute the most. This research uses qualitative methods through observation, interviews and questionnaires. The research subjects were class IV B students and social studies teachers. Data was obtained from direct observation during activities, teacher interviews, and questionnaires filled out by students. The research results show that outbound activities have a significant influence on increasing student learning outcomes and motivation. The average questionnaire score shows the